A Novel OmpR-Type Response Regulator Controls Multiple Stages of the Rhizobium etli – Phaseolus vulgaris N2-Fixing Symbiosis - Rodríguez, Susana; Correa-Galeote, David; Sánchez-Pérez, Mishael; Ramírez, Mario; Isidra-Arellano, Mariel C.; Reyero-Saavedra, María del Rocío; Zamorano-Sánchez, David; Hernández, Georgina; Valdés-López, Oswaldo; Girard, Lourdes (Frontiers in Microbiology, 2020)
OmpR, is one of the best characterized response regulators families, which includes transcriptional regulators with a variety of physiological roles including the control of symbiotic nitrogen fixation (SNF). The Rhizobium etli CE3 genome encodes 18 OmpR-type regulators; the function of the majority of these regulators during the SNF in common bean, remains elusive. In this work, we demonstrated that a R. etli mutant strain lacking the OmpR-type regulator RetPC57 (RetPC57), formed less nodules when used as inoculum for common bean. Furthermore, we observed reduced expression level of bacterial genes involved in Nod Factors production (nodA and nodB) and of plant early-nodulation genes (NSP2, NIN, NF-YA and ENOD40), in plants inoculated with RetPC57. RetPC57 also contributes to the appropriate expression of genes which products are part of the multidrug efflux pumps family (MDR). Interestingly, nodules elicited by RetPC57 showed increased expression of genes relevant for Carbon/Nitrogen nodule metabolism (PEPC and GOGAT) and RetPC57 bacteroids showed higher nitrogen fixation activity as well as increased expression of key genes directly involved in SNF (hfixL, fixKf, fnrN, fixN, nifA and nifH). Taken together, our data show that the previously uncharacterized regulator RetPC57 is a key player in the development of the R. etli - P. vulgaris symbiosis.